(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The state of the aviation transport system at international airports, in which the risks associated with aviation activities related to the operation of aircraft or directly providing such operation are reduced and maintained at an acceptable level. The safety management system, which covers the organizational structure, responsibilities, procedures, processes and provisions designed to implement the policy in the field of flight safety in air traffic services, provides the desired or acceptable level of safety and provides for the implementation of safety control.